(untitled) ("Journal "U". Economy. Management. Finance.", 2025)
The article explores the specific socio-economic features of marketing support for pharmaceutical products in the Rostov region. It analyzes the relationship between the demographic structure, income levels, the development of regional healthcare infrastructure, and the marketing strategies employed by pharmaceutical companies. The article also addresses the challenges specific to the Southern Federal District, including the high proportion of rural population, migration processes, and disease patterns. Special attention is paid to adapting national marketing campaigns to regional realities, the role of pharmacy chains as a key distribution and communication channel, and finding a balance between commercial efficiency and ensuring drug availability for all categories of citizens in the region. It is concluded that it is necessary to develop partnership models between the government, business, and the medical community in order to improve the efficiency of pharmaceutical marketing in the region.